Community Knowledge, Technology, and Assistance of Stop Open Defecation Program in Dawuhan on 2015 - Globila Nurika (JURNAL KESEHATAN LINGKUNGAN, 2018)
Based on data from the Directorate General of Environmental Health in 2006-2014 known that Situbondo triggering activities in 120 villages out of 136 villages, but the number of villages are verified as Open Defecation Free village only one village. The lowest numbers of healthy latrine ownership in 2012 was Situbondo District by 45.96%. Triggers activity of Community Lead Total Sanitation, stop Open Defecation, conducted in the Situbondo District, including in Dawuhan. Dawuhan Village is the lowest number of healthy latrines and the highest number of Open Defecation behavior in the district of Situbondo District. The aim of the study was to evaluate the implementation of stop Open Defecation program in Dawuhan. This was a cross sectional study with quantitative descriptive approach. Subjects were selected by multistage random sampling. Data collection was used questionnaire and observation. The results of this study indicate that government has fulfilled most of the resources needed to carry out the stop Open Defecation program. Otherwise, component not fulfilled yet was efforts to create a conducive environment, an increase sanitary requirement, and increase the provision of sanitation access, the lack of appropriate technology support by the government, lack of community knowledge, and no facilitator assistance. It is concluded that stop Open Defecation program in Dawuhan Village has not reached the maximum level of ODF Village because of community knowladge, technology, and less assistance activities. It is suggested to increase of socialization program, to support the appropriate technology development, and to implement facilitator assistance activity post-triggering activity.